2017
DOI: 10.1111/gcb.13734
|View full text |Cite
|
Sign up to set email alerts
|

Colour polymorphism is associated with lower extinction risk in birds

Abstract: Colour polymorphisms have played a major role in enhancing current understanding of how selection and demography can impact phenotypes. Because different morphs often display alternative strategies and exploit alternative ecological niches, colour polymorphism can be expected to promote adaptability to environmental changes. However, whether and how it could influence populations' and species' response to global changes remains debated. To address this question, we built an up-to-date and complete database on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…Broad niches, in turn, may promote establishment success, stabilize population dynamics, allow for faster range expansions, and reduce extinction risk (Bolnick et al , Forsman et al , Hughes et al , Wennersten and Forsman , Forsman , ). Consistent with these predictions, empirical evidence from experiments and comparative analyses largely suggest that variation in colour patterns, and in other traits, among individuals improves the ecological and evolutionary success of populations and species [(Lomnicki , Galeotti et al , Forsman and Åberg , Hughes et al , Krüger and Radford , Forsman and Hagman , Pizzatto and Dubey , Delhey et al , Forsman , Forsman and Wennersten , Betzholtz et al , Ducatez et al , Des Roches et al , Takahashi and Noriyuki ), but see Bolton et al () for a conflicting opinion].…”
Section: Introductionmentioning
confidence: 88%
“…Broad niches, in turn, may promote establishment success, stabilize population dynamics, allow for faster range expansions, and reduce extinction risk (Bolnick et al , Forsman et al , Hughes et al , Wennersten and Forsman , Forsman , ). Consistent with these predictions, empirical evidence from experiments and comparative analyses largely suggest that variation in colour patterns, and in other traits, among individuals improves the ecological and evolutionary success of populations and species [(Lomnicki , Galeotti et al , Forsman and Åberg , Hughes et al , Krüger and Radford , Forsman and Hagman , Pizzatto and Dubey , Delhey et al , Forsman , Forsman and Wennersten , Betzholtz et al , Ducatez et al , Des Roches et al , Takahashi and Noriyuki ), but see Bolton et al () for a conflicting opinion].…”
Section: Introductionmentioning
confidence: 88%
“…[7]). Moreover, melanin-based coloration is associated with many critical biological functions, including metabolism, reproduction, stress response and immunity [8], which can have consequences for the ability of differently coloured morphs to respond to natural and human-driven environmental changes [9][10][11]. However, the relationship between melanin-based coloration and host -parasite interactions has been understudied for a long time, thereby hindering our ability to predict the response of wild populations to changing environments and disease risk.…”
Section: Melanin-based Coloration and Changing Disease Riskmentioning
confidence: 99%
“…B 285: 20180285 thermoregulation, better ability to detoxify pollutants and/or higher competitive abilities (reviewed in [9]). As a result, colour polymorphic species might be able to respond to a wider range of environmental conditions, and colour polymorphism within a species might act as a buffer against extinction [10]. In this context, the effects of parasites on differently coloured individuals should be considered in depth.…”
Section: Melanin In a Changing World: Implications For Responses To Gmentioning
confidence: 99%
“…Although previous comparative studies have demonstrated that colour polymorphism facilitates large-scale ecological phenomena such as expansion of geographical distribution and mitigation of the extinction risk of a species [13,14], some exceptions have been highlighted [16,17]. The generality of the ecological effects of colour polymorphism with regard to ecological success remains uncertain.…”
Section: Introductionmentioning
confidence: 99%